PELATIHAN PEMBUATAN KOMPOS DARI SAMPAH ORGANIK RUMAHTANGGA DENGAN METODE TAKAKURA - Yunita Wardianti; Yuni Krisnawati (JURNAL CEMERLANG : Pengabdian pada Masyarakat, 2020)
This program aims to help the people of H. Wukirsari Village to be able to produce compost from household organic waste using the Takakura method. Wukirsari is one of the villages in Tugumulyo Subdistrict, Musirawas Regency, South Sumatra Province, which has a community including housewives who are active in planting TOGA organically but has not been supported about knowledge and skills about the process of making compost from organic waste. Yet by having the skills to make their own fertilizer can reduce the cost of purchasing fertilizers and strongly supports organic agriculture. This technology transfer on compost making is an effort to utilize household waste which usually only accumulates and creates unpleasant odors. The application of the Takakura method in composting will dispel the notion that up to now states that making compost requires a large place, is heavy carried out by housewives, and must be dirty. Therefore it is necessary to conduct compost fertilizer training using the Takakura method. To achieve this goal the methods used are observation, socialization, demonstration, training and continued with direct practice. The results of this activity are an increase in partner knowledge from an average value of initial knowledge of 40.9 and an average value of partner knowledge after training of 87.6 with an N_Gain value of 0.8 with a high category. In addition to knowledge partners also have skills in making compost using the Takakura method with an average partner skill of 93.6 and are in the very good category. The results of this activity also produced compost from household organic waste made by partners for the partners themselves.